Peran Kepemimpinan Camat Cakung dalam Meningkatkan Kinerja Pegawai pada Kantor Kecamatan Cakung Kota Administrasi Jakarta Timur - Bernadi Gamal Salam; Freddy J. Rumambi; Sri Sundari; Dwi Hermuningsih; Marisi Pakpahan (Universitas Kristen Indonesia Toraja, 2024)
The Leadership of the Cakung Subdistrict Head has a crucial role in creating positive changes in improving employee performance, work environment, and improving the quality of public services in Cakung Subdistrict. In the above context, his duties and functions as sub-district head are manifested in programs and policies. First, encourage community participation to take part in development planning within the sub-district in the development planning deliberation forum (Musrenbang), second, provide guidance and supervision of all work units, both government and private companies that have work programs and community empowerment activities in sub-district work areas, thirdly, carry out evaluations of community empowerment activities in sub-district areas, both carried out by government and private work units. The research method uses a descriptive method with a qualitative approach, namely taking data related to the problem to be researched so that it can be described descriptively, qualitatively and comprehensively, namely describing the prevailing reality and discussing the problems raised in relation to the research object, namely the role Leadership and Organizational Culture in Improving the Performance of Cakung District Office Employees, East Jakarta. From the research results, it is revealed that the Cakung sub-district head has so far fulfilled the elements of effective Leadership character which have an impact not only on aspects of employee performance, but have had a positive impact on the institutional image in a positive way or the positive image of the Cakung sub-district office in the eyes of the publik and stakeholders, especially the community in the sub-district area. Cakung. These aspects of Leadership character include aspects of the Leader as a